Fundamental study on machine tools equipped with vibration suppression mechanism based on left and right ball screw and with an ultra-high speed spindle for micro-drilling - Toshiki HIROGAKI; Eiichi AOYAMA; Tatsuya YAMASITA; Masahiro KISHIMOTO; Yuya KAWAZOE (Nihon Kikai Gakkai ronbunshu, 2017)
Recently, the miniaturization and multi-functionalization of electronic equipment have been demanded due to developments in IT. Therefore, the miniaturization and densification of the semiconductor package printed wiring boards (PWBs) have been more demanded. For the realization, the miniaturization of PWBs and fabrication of highly dense electrical circuit layers are also demanded. As a result, problems such as broken drill by the increase in aspect ratio and heat damage around the drilled hole are occurred in micro-drilling process of the PWB. A step feed drilling is considered to be effective as a solution to those problems However, it needs a high-speed reciprocating movement in short stroke to keep a drilling efficiency, and then causes residual vibration on machine tool table. In the present report, we propose a novel machine tool equipped with a counter balance mechanism using a left and right lead ball screw. This mechanism consists of a balance mass that moves in the Z-axis direction corresponding to the spindle movement to cancel a vibration force in linear direction at reciprocating movement. We construct a test stand to estimate the reducing effect of vibration force and to mode it. Moreover, we confirm the improving effect in high speed micro-drilling process with a proposed machine tool.